Bidirectional high-thermal-conductivity graphene block material and preparation method thereof

By introducing trace metal titanium or titanium nickel mixture into the graphene block and using discharge plasma sintering technology, seamless covalent bonding between graphene and metal and vertical stacking curing of multilayer graphene are achieved, solving the thermal conductivity and structural stability of traditional graphene blocks in extreme environments, and achieving the effects of bidirectional high thermal conductivity and high structural reliability.

CN119570462AActive Publication Date: 2025-03-07ZHEJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411777133.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

It is difficult for existing graphene blocks to achieve high thermal conductivity and structural stability in extreme environments, especially in the case of high heat flux and multiple cold/heat shocks, traditional bonding interfaces have pore defects and interface thermal resistance problems.

Method used

The introduction of trace metal titanium or titanium nickel mixture through ion implantation forms a nanointerface structure with seamless heterogeneous metal bonding. Combined with discharge plasma sintering technology, seamless covalent bonding of graphene and metal and vertical stacking curing of multilayer graphene are achieved.

Benefits of technology

The bidirectional high thermal conductivity of graphene blocks is achieved, the interfacial pore defects and thermal resistance are reduced, structural stability and tolerance in extreme environments are improved, and the heat flux and better actual heat dissipation ability are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570462A_ABST
    Figure CN119570462A_ABST
Patent Text Reader

Abstract

The invention discloses a bidirectional high-thermal-conductivity graphene bulk and a preparation method thereof. Trace metal is introduced to the surface of a two-dimensional graphene film through ion implantation so as to improve the wettability of graphene and metal. And then, sequentially depositing a copper nano layer and a silver nano layer on the surface of the carbide-modified graphene film formed by the trace metal to obtain the metallized graphene film. And finally, coalescing the metallized graphene film through a discharge plasma sintering technology to prepare a graphene block material. The graphene block has the characteristics of excellent molecular interface structure stability adapting to an extreme environment, in-plane and out-plane bidirectional high heat conduction performance and modular assembly compatible with industrial production, and large-scale production of any thickness, area and shape is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of extreme environment thermal management material preparation, and specifically relates to a bidirectional high thermal conductivity graphene block material and a preparation method thereof. Background Art

[0002] With the rapid development of high-power electronic devices in the fields of communications, aerospace, military and energy storage, higher requirements are placed on their integration and miniaturization. However, it is inevitable that local hot spots with high heat flux density are easily generated during the operation of electronic equipment, posing a great threat to the stable and reliable operation of electronic equipment. In addition, under some extreme service conditions, such as deep low temperature-high temperature alternation, high-energy rays, high vacuum, etc., traditional electronic thermal management modules face the risk of catastrophic structural failure. Therefore, the development of new thermal management materials is crucial to explore the next generation of aerospace thermal control technology to meet the stringent requirements of lightweight, high thermal conductivity and excellent structural stability under extreme application conditions.

[0003] Graphene-based films and bulk materials inherit the excellent properties of two-dimensional graphene sheet assembly units, such as high thermal conductivity, low density, high flexibility, low thermal expansion coefficient and stable physical and chemical properties. They are a type of carbon-based thermal management material with great potential and have been favored in the aerospace and electronics fields in recent years. They are mainly obtained through various bottom-up macroscopic assembly methods such as wet scraping, filtration, wet spinning, centrifugal casting, etc. However, traditional graphene films and bulk materials are subject to the intrinsic contradiction between high thermal conductivity and large thickness. Their own heat flux (the product of thermal conductivity and thickness) is still low, and they cannot effectively solve the high heat flux (usually higher than 1000 W / cm 2 ) problem, it is urgent to develop graphene bulk materials with high thermal conductivity and a thickness of hundreds of microns.

[0004] Specifically, the graphite block prepared by directly pressing natural graphite powder has a macroscopic in-plane thermal conductivity of less than 600 W / mK due to the internal multi-grain boundary defects that hinder the internal phonon transmission, making it difficult to meet the actual heat dissipation application needs; it is difficult to prepare graphene blocks based on graphene-based solutions by direct scraping, mainly because of the low solid content characteristics of the solution, which makes it difficult to make thick graphene blocks. At the same time, when the graphene block undergoes a liquid-solid two-phase drying transition, there is an unavoidable capillary shrinkage effect that makes the internal graphene sheets of the wet block poorly oriented and takes a long time to dry. The thermal conductivity and structural stability of the resulting graphene block have bottlenecks, making it difficult to meet the needs of actual applications.

[0005] At present, graphene blocks are generally made by stacking and bonding several high thermal conductivity graphene films with polymer adhesives, and then curing by cold pressing or vacuum heating to eliminate the pores at the bonding interface. However, the graphene blocks prepared by this method still face many problems in practical applications. First, the bonding between graphene film and polymer adhesive is mainly through van der Waals force, resulting in weak interface bonding and more pores, which makes the interface thermal resistance increase sharply. Second, because graphene film is an anisotropic material, its out-of-plane thermal conductivity is extremely low (less than 5 W / (mK)), and the polymer adhesive with lower thermal conductivity (1-2 W / (mK)) cannot improve its out-of-plane heat transfer ability, and further reduce the out-of-plane phonon heat transfer, which is not conducive to rapid heat transfer. Third, the graphene blocks prepared by traditional polymer bonding method have poor tolerance in extreme environments. After multiple cold / hot shocks, the polymer layer is prone to aging, and the graphene blocks have serious structural failure behaviors such as bubbling, delamination, and easy wrinkling and fragility on the surface, which greatly reduces its heat transfer performance. Furthermore, through the self-fusion method or electric heating fusion method mediated by the surface oxygen-containing functional groups of graphene oxide, effective bonding of multilayer graphene films can be achieved, thereby realizing the preparation of graphene bulk materials. However, both methods cannot guarantee the proper fitting of the interface of the graphene film unit, resulting in many defects in the interface pore structure. Moreover, the interlayers of the graphene bulk material are still van der Waals stacking, which makes it difficult to achieve efficient out-of-plane transfer of phonons, and its macroscopic vertical thermal conductivity is still limited to less than 5 W / mK. In addition, this method is subject to delicate operations for fitting, and it is difficult to achieve large-scale industrial production.

[0006] Therefore, it is still a huge challenge to develop bidirectional high thermal conductivity and structurally stable graphene blocks with a thickness of more than hundreds of microns to ensure the long-term stable service performance of graphene blocks in extreme environments. Summary of the invention

[0007] In view of the difficulties in the above-mentioned prior art, the present invention proposes a bidirectional high thermal conductivity graphene block material and a preparation method thereof. The material has a seamless heterogeneous metal bonding nano-interface structure, which effectively eliminates the pore defects existing in the traditional graphene bonding interface and reduces the interface phonon scattering effect. On the one hand, this method realizes the seamless covalent bonding of the graphene / metal heterogeneous interface, ensuring that it forms a stable material structure after multiple extreme cold / heat shocks (77-573 K). On the other hand, the graphene block material benefits from the interlayer interface coupling effect, and phonons can be effectively and efficiently transmitted across layers, thus having unique in-plane and out-of-plane bidirectional high thermal conductivity characteristics, breaking through the anisotropic limitations of existing graphene films and bulk materials, so that it has a larger heat flux and exhibits better actual heat dissipation capabilities.

[0008] One of the technical solutions of the present invention is to provide a method for preparing a bidirectional high thermal conductivity graphene block material, wherein trace metal titanium or a metal titanium-nickel mixture is introduced on the surface of the graphene film by ion implantation to improve the wettability of graphene with metal, and the trace metal layer component includes a metal element that can form a covalent bond with carbon atoms in the graphene to reduce the interface phonon thermal resistance. Then, copper and silver nanolayers are sequentially magnetron sputtered on the surface of the two-dimensional graphene film modified with trace metal titanium or a metal titanium-nickel mixture to obtain a metallized two-dimensional graphene film. Finally, the metallized two-dimensional graphene film is polymerized by a discharge plasma sintering technique to form a graphene block material.

[0009] The specific steps are as follows: (1) Clean the graphene membrane. Generally, ultrasonically clean it in acetone and alcohol solution for 15 minutes, then rinse it with deionized water and dry it naturally to remove various impurities introduced during the preparation process. (2) implanting metal ions on the upper and lower surfaces of the graphene film to form a carbide bridging layer; the metal ions are one or two of titanium, nickel, iron, and tungsten, and the thickness is 10 nm; (3) Then, a metal copper layer and a silver layer are sequentially deposited on the bridging layer; wherein the thickness of the copper layer is 10-250 nm, and the thickness of the silver layer is 10-50 nm; and a metallized graphene film is obtained; (4) Cutting the metallized graphene films, filling them into a clean graphite mold one by one, and vertically stacking and solidifying the multilayer metallized graphene films using a spark plasma sintering process to produce a bidirectional high thermal conductivity graphene block.

[0010] Furthermore, the graphene film in step (1) is one of a pure graphene film and a graphene-based composite film.

[0011] Furthermore, the ion implantation method in step (2) is to use a titanium target, a nickel target, an iron target, a tungsten target, or a titanium-nickel composite metal target to sputter a metal ion beam onto the surface of the graphene film. The incident ions covalently bridge with the carbon atoms on the surface of the graphene film to form a carbide transition layer to enhance the interface bonding strength and eliminate interface pore defects, and lay an excellent interface structure foundation for a seamless and firm graphene / metal interface.

[0012] Furthermore, the vertical stacking solidification method in step (4) is a vacuum degree of less than 1×10 -3 Pa, and a thermocouple gradient heating method was used under a uniaxial pressure of 10 MPa, that is, from room temperature to 400 ℃ in 4 minutes, and then to 500 ℃ in another 4 minutes, and kept at 500 ℃ for 10 minutes, then the heating was stopped, and it was naturally cooled in the cavity. The high vacuum condition remained unchanged during the whole process.

[0013] This method is mature and simple. Based on the stacked modular design of multi-metals, it can use the carbide bridging layer generated by covalent bonding to achieve seamless interface connection, thereby reducing the interfacial thermal resistance caused by the traditional van der Waals interface, improving the out-of-plane heat transfer performance of the graphene block and weakening the strong anisotropy of the graphene block.

[0014] The macroscopic heat transfer performance of graphene bulk is closely related to its internal graphene interface structure. The interaction between the layers of traditional graphene bulk is dominated by van der Waals forces, which makes the phonon interlayer transport energy barrier high and prone to boundary scattering effects. At the same time, there are a large number of structural defects at the interface of traditional polymer-bonded graphene bulk. The point defect scattering of phonons at the interface significantly dominates the in-plane thermal conductivity, which will further reduce the thermal conductivity of carbonaceous materials at low temperatures. Combining nano-heterogeneous metals with the graphene surface to generate a seamless molecular interface bridging layer is conducive to reducing the interface nanopore defects, thereby effectively increasing the mean free path of phonons in the interlayer direction and reducing the out-of-plane interface thermal resistance.

[0015] At the same time, due to the atomic lattice mismatch between copper atoms and carbon atoms, the two are insoluble in each other, and it is impossible to directly achieve a strong interface seamless connection between the nano copper layer and graphene. The phonon vibration spectra of metallic copper and graphene are also very different, resulting in the existence of Kapitza thermal resistance. When high-energy phonons cross the interface of graphene-metallic copper, they need to transfer energy to the interface of the next layer of material through more coupled vibrations, which causes serious attenuation of phonon energy. Direct compounding will cause great interfacial thermal resistance, and the out-of-plane and in-plane heat transfer efficiency will be greatly affected. Therefore, the molecular carbide interface bridging layer can effectively match the interface phonon vibration spectrum of the graphene-metal interface and optimize the interface phonon transmission behavior, ensuring the mean free path of phonons in the out-of-plane perpendicular direction and the phonon transmission speed.

[0016] In addition, traditional graphene blocks mainly rely on the phonon thermal conduction mechanism. The additionally introduced metal layer can also improve the electronic thermal conductivity contribution of the graphene block material, and has a dual transmission mechanism of phonons and electrons, thereby greatly improving the in-plane and out-of-plane thermal conductivity of the graphene block. At the same time, the multi-metal layer has better ductility and can be used as a packaging layer. It can also further reduce the structural instability of the traditional graphene block caused by the van der Waals weak interaction, which is easy to dissociate the layered structure, thereby improving the structural reliability of the graphene block under extreme conditions of use and ensuring long-term efficient heat dissipation performance.

[0017] The second technical solution of the present invention is to provide a bidirectional high thermal conductivity graphene block prepared by the above-mentioned preparation method. The block has a seamless heterogeneous metal bonding nano-interface structure, which effectively eliminates the pore defects existing in the traditional bonding interface and reduces the interface phonon scattering effect. The prepared bidirectional high thermal conductivity graphene block has a controllable thickness from micron level to millimeter level, has strong structural designability, and has high structural tolerance in extreme environments, and has great application potential in the field of extreme thermal management.

[0018] The material is composed of alternating stacks of micron-scale two-dimensional graphene films and nano-scale multi-metal layers. Specifically, the two-dimensional graphene film has a thickness of 1 to 150 μm, an in-plane thermal conductivity of 1000 to 2000 W / (mK), and a volume fraction of 90 to 99.5% in the bulk material. The nano-scale multi-metal layer includes a bridging layer, a heat-conducting layer, and a welding layer; the bridging layer is one of titanium carbide, nickel carbide, iron carbide, tungsten carbide, or a carbide of a titanium-nickel mixture with a thickness of 10 nm; in the titanium-nickel mixture, the mass fraction of nickel is 60%; the heat-conducting layer is metallic copper with a thickness of 10-250 nm; the welding layer is metallic silver with a thickness of 10-50 nm.

[0019] Beneficial effects of the present invention: (1) Multiple two-dimensional graphene films are vertically stacked and solidified by using multi-element nanometal layers, transforming the traditional van der Waals adhesion into heterogeneous metal covalent bonding, thus achieving seamless connection between high thermal conductivity two-dimensional graphene film elements, making the graphene block have a lower interface pore defect structure and greatly improved interface connection strength.

[0020] (2) Based on this reliable seamless connection engineering, the graphene block achieves high in-plane thermal conductivity and good out-of-plane heat transfer, making it a competitive new thermal management material.

[0021] (3) The obtained graphene block has good tolerance to extreme high and low temperature environments and structural stability. After hundreds of high / low temperature shocks (77 K~573 K), it still maintains excellent assembly structure and thermal conductivity, and is expected to be used in aerospace and other fields.

[0022] (4) The obtained graphene block has a low density and controllable shape and size, and can be adjusted according to actual needs to adapt to more extreme thermal management application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Flow chart of the preparation of conventionally bonded graphene blocks and seamlessly bonded bidirectional high thermal conductivity graphene blocks; Figure 2 SEM images of the surface and cross section of a single metallized graphene film; Figure 3 Physical picture of bidirectional high thermal conductivity graphene block; Figure 4 Comparison of interface porosity between Example 1 and Comparative Example 1; Figure 5 Effect of low temperature shock on the in-plane thermal conductivity of graphene bulk materials in Example 2 and Comparative Example 2; Figure 6Comparison of the effects of low temperature shock on the appearance of graphene blocks in Example 2 and Comparative Example 2; Figure 7 Effect of high temperature shock on the in-plane thermal conductivity of graphene bulk materials of Example 3 and Comparative Example 3; Figure 8 Effect of high temperature shock on the appearance of graphene blocks in Example 3 and Comparative Example 3. DETAILED DESCRIPTION

[0024] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0025] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0026] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0027] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0028] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0029] The purity of the metal target materials described in the present invention is >99%.

[0030] Example 1 (1) The graphene film (thickness 25 μm, in-plane thermal conductivity 1900 W / (mK)) was ultrasonically cleaned in acetone and alcohol solutions for 15 min respectively, then rinsed with deionized water and dried naturally to remove various impurities introduced during the preparation process.

[0031] (2) Metal ion implantation on the surface of the graphene film. First, the graphene film is cleaned with argon ions and the vacuum degree in the cavity is less than 5 10 -3Pa, argon flow rate of 15 sccm, bias voltage of 400 V, temperature of 150°C, injection energy of 30 kV, duration of 10 minutes. Then, using a titanium-60 wt% nickel composite metal target (purity>99%), the injected metal ions reacted in situ with the carbon atoms on the surface of the graphene film to form a carbide transition layer with a thickness of 10 nm.

[0032] (3) Depositing multiple layers of metal on the graphene film modified with the metal titanium nickel molecular bridge layer by magnetron sputtering technology. The output power is 2 kW, using a metal copper target (purity> 99%) and a silver target (purity> 99%), depositing a metal copper layer with a thickness of 245 nm and a metal silver layer with a thickness of 25 nm, respectively. The entire process is carried out under vacuum protection. The two sides of the graphene film are treated in the same way to obtain a metallized graphene film (such as Figure 2 ).

[0033] (4) Cut a single metallized graphene film into discs to meet the thermal conductivity test requirements. Take 20 cut circular films, stack them vertically one by one in a clean graphite mold, and use the spark plasma sintering process to obtain vertically stacked solidified graphene blocks (such as Figure 3 The curing sintering adopts a gradient heating method, that is, from room temperature to 400 °C, the heating time is 4 minutes; then the temperature is raised to 500 °C in 4 minutes, and kept at 500 °C for 10 minutes, and then the temperature is stopped and the cavity and sample are cooled naturally, and the vacuum degree is kept below 1×10 -3 Pa, and apply a vertical pressure of 10 MPa to ensure complete curing.

[0034] The thickness of the graphene block is 505 μm, the in-plane thermal conductivity is 1649 W / (mK), the out-of-plane thermal conductivity is 8.88 W / (mK), and the in-plane electrical conductivity is 8.64×10 5 S / m. Figure 4 It can be observed that this embodiment has a dense and continuous graphene-metal interface layer and metal-metal interface layer. The filling of the pores by the carbide layer and the metal atoms significantly eliminates the interface defects, and the interface porosity is reduced to 1 / 6 of that in comparative example 1, effectively achieving covalent seamless connection between the graphene layer and the metal layer.

[0035] Example 2 The same as Example 1, except that 40 cut circular films are taken, and they are vertically stacked one by one in a clean graphite mold, and a spark plasma sintering process is used to obtain a vertically stacked and solidified graphene block.

[0036] After multiple low temperature shocks, the macrostructure of this embodiment remains basically unchanged ( Figure 6 ) Example 3 The same as Example 1, except that 60 cut circular films are taken, and they are stacked vertically one by one in a clean graphite mold, and a spark plasma sintering process is used to obtain a vertically stacked and solidified graphene block.

[0037] After 200 high temperature shock cycles (298 K ~ 573 K), the thermal conductivity of this embodiment still maintained 95%, and the original structure was still maintained after multiple high temperature thermal shocks ( Figure 8 ).

[0038] Example 4 The same as Example 1, except that the graphene film (thickness of 70 μm, in-plane thermal conductivity of 1700 W / (mK)) is used. 15 cut circular films are stacked vertically one by one in a clean graphite mold, and a vertically stacked solidified graphene block is obtained by spark plasma sintering. The graphene block has a thickness of 1033 μm, an in-plane thermal conductivity of 1462 W / (mK), an out-of-plane thermal conductivity of 8.32 W / (mK), and an in-plane electrical conductivity of 7.68×10 5 S / m.

[0039] Example 5 Same as Example 1, except that the graphene film (thickness of 150 μm, in-plane thermal conductivity of 1500 W / (mK)) was taken, 7 cut circular films were stacked vertically one by one in a clean graphite mold, and a vertically stacked solidified graphene block was obtained by spark plasma sintering process. The graphene block has a thickness of 1025 μm, an in-plane thermal conductivity of 1284 W / (mK), an out-of-plane thermal conductivity of 8.25 W / (mK), and an in-plane electrical conductivity of 6.75×10 5 S / m.

[0040] Example 6 Same as Example 1, except that iron is used as the bridging layer in step (2). The obtained graphene block has an in-plane thermal conductivity of 1630 W / (mK) and an out-of-plane thermal conductivity of 8.18 W / (mK).

[0041] Example 7 The same as Example 1, except that tungsten is used as the bridging layer in step (2). The obtained graphene block has an in-plane thermal conductivity of 1672 W / (mK) and an out-of-plane thermal conductivity of 8.68 W / (mK).

[0042] Example 8 The same as Example 1, except that the functional layer is made of high thermal conductivity copper metal with a thickness of about 10 nm; the welding layer is made of soft and low melting point silver metal with a thickness of about 10 nm.

[0043] Example 9 The same as Example 1, except that the functional layer is made of high thermal conductivity copper metal, 250 nm thick; the welding layer is made of soft and low melting point silver metal, about 50 nm thick.

[0044] Comparative Example 1 The preparation method of conventional graphene block material specifically comprises the following steps: (1) The graphene film (thickness 25 μm, in-plane thermal conductivity 1900 W / (mK)) was ultrasonically cleaned in acetone and alcohol solutions for 15 min respectively, then rinsed with deionized water and dried naturally to remove various impurities introduced during the preparation process.

[0045] (2) 20 graphene films were bonded layer by layer using an ultra-thin polymer double-sided tape with a thickness of 1 μm to obtain a polymer-bonded graphene block. The tape uses an ultra-thin polyethylene terephthalate transparent substrate and is coated on both sides with a polyacrylate-based polymer adhesive.

[0046] (3) Cold press the above samples at 10 MPa for 12 hours to improve the compactness. Cut the samples into disc shapes suitable for testing.

[0047] The thickness of the prepared graphene block is 513 μm, the in-plane thermal conductivity is 1513 W / (mK), the out-of-plane thermal conductivity is 1.82 W / (mK), and the in-plane electrical conductivity is 1.43×105 S / m (as shown in Table 1).

[0048] like Figure 4 As shown, there are a large number of fine wrinkles on the surface of the graphene film, which is difficult to achieve conformal adhesion assembly with the polymer, so that the graphene and polymer interface of this comparative example has a large number of pore defects, and the porosity can reach 12%. These unavoidable pores are easily filled with adiabatic air in actual use, so that there is a huge interfacial thermal resistance inside the graphene block. And a large number of interfacial pore defects are easily formed under the action of external forces. Local stress centers are caused, which is the root cause of the destruction of the polymer adhesive-based graphene block structure under extreme conditions.

[0049] Comparative Example 2 The same as comparative example 1, except that 40 graphene films are bonded layer by layer.

[0050] After testing, the thickness of Example 2 is 1009 μm, the in-plane thermal conductivity is 1507 W / (mK), the out-of-plane thermal conductivity is 8.53 W / (mK), and the in-plane electrical conductivity is 7.92×10 5 The thickness of comparative example 2 is 1024 μm, the in-plane thermal conductivity is 1228 W / (mK), the out-of-plane thermal conductivity is 1.67 W / (mK), and the in-plane electrical conductivity is 1.16×10 5 S / m.

[0051] like Figure 5 In order to verify the structural tolerance and performance stability of the obtained graphene block in a low-temperature environment, a simulated low-temperature cyclic impact experiment was carried out with liquid nitrogen, and the graphene block samples were tested multiple times in the temperature range of 77 K to 298 K. After 200 low-temperature impacts, the in-plane thermal conductivity of Comparative Example 2 decreased by 70%, while the in-plane thermal conductivity of Example 2 remained stable. This is due to the fact that the seamless metal nanolayer of Example 2 effectively reduces the interface porosity and blocks the penetration of liquid nitrogen molecules at the pore defects of the graphene film assembly interface, thereby avoiding the huge deformation of liquid helium molecules due to the gas-liquid phase change, and inhibiting the destructive damage of the traditional polymer adhesive-based graphene block, such as bubbling between graphene layers and structural dissociation.

[0052] Comparative Example 3 The same as comparative example 1, except that 60 graphene films are bonded layer by layer to obtain a bonded graphene block. After testing, the thickness of Example 3 is 3026 μm, the in-plane thermal conductivity is 1336 W / (mK), the out-of-plane thermal conductivity is 8.11 W / (mK), and the in-plane electrical conductivity is 7.07×10 5 The thickness of comparative example 3 is 3073 μm, the in-plane thermal conductivity is 978 W / (mK), the out-of-plane thermal conductivity is 1.04 W / (mK), and the in-plane electrical conductivity is 0.92×10 5 S / m.

[0053] The thermal stability of graphene bulk materials is crucial to their performance and service life in high temperature scenarios. Figure 7 As shown in the figure, after 200 high temperature shock cycles (298 K ~ 573 K), the in-plane thermal conductivity of Comparative Example 3 dropped sharply by nearly 80%, while that of Example 3 remained at 95%. This is because the polymer adhesive is easily thermally decomposed at high temperatures, and the interlayer adhesion of Comparative Example 3 was lost after multiple thermal shocks, and the interlayer adhesion structure was significantly destroyed. However, because the graphene film and the nanometal layer have a seamless covalent bonding interface, Example 3 still maintains its original structure after multiple high temperature thermal shocks, which further proves that the graphene block assembled based on covalent seamless bonding has excellent high temperature tolerance.

[0054] Comparative Example 4 The same as comparative example 1, except that the graphene film (thickness of 70 μm, in-plane thermal conductivity of 1700 W / (mK)) was bonded layer by layer to obtain a polymer adhesive-based graphene block.

[0055] The graphene block prepared in this comparative example has a thickness of 1049 μm, an in-plane thermal conductivity of 1251 W / (mK), an out-of-plane thermal conductivity of 1.46 W / (mK), and an in-plane electrical conductivity of 1.18×10 5 S / m.

[0056] Comparative Example 5 The same as comparative example 1, except that the graphene film (thickness of 150 μm, in-plane thermal conductivity of 1500 W / (mK)) is used, 7 graphene films are bonded layer by layer to obtain a polymer-bonded graphene block.

[0057] The graphene block prepared in this comparative example has a thickness of 1041 μm, an in-plane thermal conductivity of 1095 W / (mK), an out-of-plane thermal conductivity of 1.20 W / (mK), and an in-plane electrical conductivity of 1.03×10 5 S / m.

[0058] Comparative Example 6 Same as Example 1, except that the sputtering order of the metal in step 3 is 245 nm of the metal silver layer and 25 nm of the metal copper layer. The obtained graphene block has an in-plane thermal conductivity of 1640 W / (mK) and an out-of-plane thermal conductivity of 7.88 W / (mK).

[0059] Comparative Example 7 Same as Example 1, except that in step 3, a 245 nm metal iron layer is first sputtered, and then a 25 nm metal silver layer is sputtered. The obtained graphene block has an in-plane thermal conductivity of 1554 W / (mK) and an out-of-plane thermal conductivity of 7.78 W / (mK).

[0060] Comparative Example 8 Same as Example 1, except that the thickness of the sputtered copper layer in step 3 is 5 nm. The obtained graphene block has an in-plane thermal conductivity of 1354 W / (mK) and an out-of-plane thermal conductivity of 6.76 W / (mK).

[0061] Comparative Example 9 Same as Example 1, except that the thickness of the sputtered silver layer in step 3 is 100 nm. The obtained graphene block has an in-plane thermal conductivity of 1454 W / (mK) and an out-of-plane thermal conductivity of 7.16 W / (mK).

[0062] Table 1 Thickness, density, thermal conductivity and electrical conductivity of each embodiment and comparative example Material Thickness (μm) Density (g / cm3) In-plane thermal conductivity (W / mK) Out-of-plane thermal conductivity (W / mK) <![CDATA[In-plane conductivity (×10 5 S / m)]]> Example 1 505 2.45 1649±158 8.88±0.72 8.64±0.75 Comparative Example 1 513 1.91 1513±112 1.82±0.15 1.43±0.12 Example 2 1009 2.45 1507±148 8.53±0.77 7.92±0.51 Comparative Example 2 1024 1.91 1228±111 1.67±0.13 1.16±0.10 Example 3 3026 2.45 1336±132 8.11±0.64 7.07±0.43 Comparative Example 3 3073 1.91 978±87 1.04±0.09 0.92±0.07 Example 4 1033 2.27 1462±139 8.32±0.71 7.68±0.56 Comparative Example 4 1049 1.92 1251±105 1.46±0.10 1.18±0.11 Example 5 1025 2.21 1284±99 8.25±0.71 6.75±0.43 Comparative Example 5 1041 1.93 1095±83 1.20±0.11 1.03±0.09 It can be seen from Table 1 that, under the conditions of the same graphene film thickness and number of stacking layers, the graphene block prepared by the preparation method used in the present invention has significantly improved in-plane and out-of-plane thermal conductivity and in-plane electrical conductivity compared to the graphene block prepared by polymer bonding using the traditional method.

[0063] Table 2 Effects of the types and thickness parameters of the bridging layer, thermal conductive layer, and welding layer on the properties of graphene bulk materials Material Bridge Layer Thermally conductive layer Welding layer Thermal conductive layer thickness (nm) Welding layer thickness In-plane thermal conductivity Out-of-plane thermal conductivity Example 1 Ti-Ni Cu Ag 245 25 1649±158 8.88±0.72 Example 6 Fe Cu Ag 245 25 1630±135 8.18±0.42 Example 7 W Cu Ag 245 25 1672±135 8.68±0.37 Comparative Example 6 Ti-Ni Ag Cu 245 25 1640±132 7.88±0.66 Comparative Example 7 Ti-Ni Fe Ag 245 25 1554±78 7.78±0.45 Comparative Example 8 Ti-Ni Cu Ag 5 25 1354±97 6.76±0.75 Comparative Example 9 Ti-Ni Cu Ag 245 100 1454±127 7.16±0.32 As can be seen from Table 2, the composition, thickness and stacking order of the bridging layer, thermal conductive layer and welding layer in the graphene block have a significant effect on the graphene block. The graphene block obtained by the preparation method of the present invention forms a covalent interface bridging layer and a thermal conductive layer and welding layer of appropriate thickness, which significantly improves the in-plane and out-of-plane thermal conductivity and in-plane electrical conductivity of the graphene block.

[0064] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.

Claims

1. A method for preparing a bidirectional high thermal conductivity graphene block, characterized in that: The following steps are involved: (1) Clean the graphene film and let it dry naturally; (2) metal ion implantation is performed on the upper and lower surfaces of the graphene film to form a bridging layer; the metal ions are one or two of titanium, nickel, iron, and tungsten, and the thickness thereof is 10 nm; (3) Then, a metal copper layer and a silver layer are sequentially deposited on the bridging layer; wherein the thickness of the copper layer is 10-250 nm, and the thickness of the silver layer is 10-50 nm; and a metallized graphene film is obtained; (4) Cutting the metallized graphene films, filling them into a graphite mold one by one, and vertically stacking and solidifying the multilayer metallized graphene films using a spark plasma sintering process to produce a bidirectional high thermal conductivity graphene block.

2. The preparation method according to claim 1, characterized in that: The graphene film in step (1) is one of a pure graphene film and a graphene-based composite film.

3. The preparation method according to claim 1, characterized in that: The ion implantation method in step (2) is to use a titanium target, a nickel target, an iron target, a tungsten target, or a titanium-nickel composite metal target to sputter a metal ion beam onto the surface of the graphene film.

4. The preparation method according to claim 1, characterized in that: The vertical stacking solidification method in step (4) is performed with a vacuum degree of less than 1×10 -3 Pa, and a thermocouple gradient heating method was used under a uniaxial pressure of 10 MPa, that is, from room temperature to 400 °C in 4 minutes, and then to 500 °C in another 4 minutes, and maintained at 500 °C for 10 minutes, then the heating was stopped and naturally cooled in the cavity.

5. A bidirectional high thermal conductivity graphene block prepared by the preparation method according to claim 1, characterized in that: It is composed of graphene films and nano-scale multi-metal layers stacked alternately; the nano-scale multi-metal layers include a bridging layer, a thermal conductive layer and a welding layer; the bridging layer is one of titanium carbide, nickel carbide, iron carbide, tungsten carbide with a thickness of 10 nm or a carbide of a titanium-nickel mixture with a thickness of 10 nm; the mass fraction of nickel in the titanium-nickel mixture is 60%; the thermal conductive layer is metallic copper with a thickness of 10-250 nm; the welding layer is metallic silver with a thickness of 10-50 nm.

6. The bidirectional high thermal conductivity graphene block material according to claim 5, characterized in that: The volume fraction of the graphene film in the bidirectional high thermal conductivity graphene block is 90-99.5%.

Citation Information

Patent Citations

  • Graphene-nano copper composite material heat conduction film and preparation method thereof

    CN106082186A

  • High-thermal conductivity graphene thick film and preparation method thereof

    CN107140619A

  • High-thermal-conductivity graphene film and preparation method thereof

    CN112760082A

  • Thickness-controllable high-performance graphene film and preparation method thereof

    CN112978719A

  • Efficient light flexible heat conduction chain based on graphene macroscopic assembly film

    CN112980400A